Informe de actividades realizadas para el proyecto PNR-CIAT en los departamentos de Cesar, Guajira y Magdalena - Sánchez, C.A. (International Center for Tropical Agriculture, 1991)
In the departments of Cesar, Guajira, and Magdalena, the feasibility study for a cassava natural drying plant of 1000 m(2) in Curumani, Cesar, was concluded. The Codazzi Workers` and Farmers` Cooperative (COOTRADECO Ltda.) will be responsible for its operation. Four demonstration plants were established, 3 in Cesar and 1 in Guajira. A proposal was also made to establish seed production plots. Trials with new CIAT var. continued for comparison with local var. (AS (extract)-CIAT)